Perceptions of psychological momentum of elite soccer players - Redwood-Brown, A. J.; Sunderland, C. A.; Minniti, A. M.; O`Donoghue, P. G. (International Journal of Sport and Exercise Psychology, 2018)
The purpose of this research was to investigate elite soccer players` perceptions and experiences of psychological momentum (PM) using a mixed methodological approach. Specifically, by comparing responses, the study aimed to provide coaches with a more appropriate method for collecting PM data. Interviews and focus groups were conducted with 10 English Academy, elite male soccer players. In addition, 75 professional male soccer players completed a 49-item measure about their experiences of PM. Interviews and focus groups were manually analysed using a combination of inductive and deductive approaches with Chi-square tests used to assess differences between responses to the PM measure. The majority of questionnaire responses were supported by themes highlighted by players interviewed. Scoring and conceding goals were the most frequently reported match variables associated with positive and negative PM, respectively. In addition, "feeling confident", "having a positive attitude" and "being cohesive as a team" were important aspects of positive PM. A "perceived lack of ability" and "feeling anxious" were the most frequently reported experiences of negative PM. The similarity of results from both methods support the measure as a useful tool for coaches to collect data pertaining to players` experiences and perceptions of PM. Overall, findings suggest that PM is a complex (dynamic) process whereby triggers, characteristics, and consequences can hardly be separated. By understanding players` experiences and perceptions of PM, coaches may incorporate specific training methods to help players maximise positive PM, reduce negative PM as well as develop strategies to optimise PM.